GEMBYUNG BUHUN ART PACKAGING IN A PERFORMANCE AT THE EDUCATIONAL TOURISM VILLAGE CISAAT-CIATER SUBANG REGENCY - Cahyadi, Ojang; Suwandi, Tuteng; Haerudin, Deden (International Journal of Performing Arts (IJPA), 2023)
Gembyung is a traditional art that uses large drums/tambourines as the main tool. Gembyung at the time of the performance displays traditional music and the music that is sung also contains sacred and solemn elements. This is firmly held by the Gembyung players to maintain the authenticity of the traditional arts passed down by their ancestors. Gembyung is a percussion instrument made of leather and wood. Based on the onomatopoeia (word follows sound), the word Gembyung comes from the sound of the percussion pattern gem (beat and hold) and byung (beat and release). At first the Gembyung Subang art developed in the pesantren environment. This Gembyung is usually performed at ceremonies of Islamic religious activities such as the commemoration of the Prophet's Birthday, Rajaban and Activities 1 Syuro which are held around places of worship. In the development of Gembyung, there has also been a change in the form of packaging in the presentation of performances as the goal of research on works of art. The research methodology is qualitative which is oriented towards works of art as a result of packaging products and innovative works, to be applied to performances in general in society.